The Effect of CSR Disclosure, Firm Size, Capital Intensity, and Inventory Intensity on Tax Aggressiveness - Rahayu, Silvia; Suryarini, Trisni (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the effect of CSR disclosure, firm size, capital intensity, and inventory intensity on tax aggressiveness. This study uses a population of 63 companies in the basic and chemical industrial sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2015-2018. The sampling technique in this study was the purposive sampling method, resulting in a final sample of 29 companies with 89 units of analysis after deducting 27 outlier data. This research uses descriptive statistical analysis method and inferential statistical analysis, namely multiple regression analysis. The results showed that partially CSR disclosure has a positive and significant effect on tax aggressiveness. Meanwhile, firm size, capital intensity, and inventory intensity do not affect tax aggressiveness. Simultaneously, all dependent variables affect tax aggressiveness. It can be concluded that CSR disclosure can determine the level of tax aggressiveness by the company. This means that the higher the CSR disclosure made by the company, the higher the level of tax aggressiveness carried out by the company. Keywords: CSR Disclosure; Firm Size; Capital Intensity; Inventory Intensity; Tax Aggressiveness